General chemistry : the essential concepts - Chang, Raymond; Goldsby, Kenneth A. (New York : McGraw-Hill Education, 2014)
Presenting only the material that is essential for a one-year general chemistry course, this book incorporates real-world examples; helping students visualize the three-dimensional atomic and molecular structures that are the basis of chemical activity; and developing problem-solving and critical thinking skills.
1 Introduction 2 Atoms, Molecules, and Ions 3 Stoichiometry 4 Reactions in Aqueous Solutions 5 Gases 6 Energy Relationships in Chemical Reactions 7 The Electronic Structure of Atoms 8 The Periodic Table 9 Chemical Bonding I: The Covalent Bond 10 Chemical Bonding II: Molecular Geometry and Hybridization of Atomic Orbitals 11 Introduction to Organic Chemistry 12 Intermolecular Forces and Liquids and Solids 13 Physical Properties of Solutions 14 Chemical Kinetics 15 Chemical Equilibrium 16 Acids and Bases 17 Acid-Base Equilibria and Solubility Equilibria 18 Thermodynamics 19 Redox Reactions and Electrochemistry 20 The Chemistry of Coordination Compounds 21 Nuclear Chemistry 22 Organic Polymers--Synthetic and Natural Appendix 1 Units for the Gas Constant Appendix 2 Selected Thermodynamic Data at 1 atm and 25 degrees Centigrade Appendix 3 Mathematical Operations Appendix 4 The Elements and the Derivation of Their Names and Symbols
Includes index.
Previous edition ©2011, 2008 and 2006.
1259073769 (MHID)
PHR
Trim Education
Keywords: Chemistry -- Textbooks; Chemistry; Pharmacy